2019
DOI: 10.1002/cplu.201900274
|View full text |Cite
|
Sign up to set email alerts
|

Phthalimide‐Based Transparent Electron‐Transport Materials with Oriented‐Amorphous Structures: Preparation from Solution‐Processed Precursor Films

Abstract: A star‐shaped molecule featuring three phthalimide units attached to a triazine core was designed as an electron‐transport material. Solution processing was achieved by preparing a precursor molecule bearing tert‐butoxycarbonyl (Boc) substituents, which are afterwards removed by annealing. The annealed film is transparent to visible light, with an absorption edge of 339 nm. Two‐dimensional grazing incidence X‐ray diffraction (2D‐GIXD) and p‐polarized multiple‐angle incidence resolution spectrometry (pMAIRS) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Our group reported the highly oriented structure of Nafion thin films on SiO x [34], MgO [35,36], sputtered Pt [37], and sputtered Au [36] surfaces by infrared p-polarized multiple-angle incidence resolution spectrometry (pMAIRS), which was developed by Hasegawa and co-workers [38][39][40], as presented in Figure 2(a-d). IR pMAIRS offers the molecular orientation for each functional group to various functional materials such as derivatives of polythiophene [41,42], porphyrin [43], pentacene [44], fullerene [45], naphthalene diimide [46], phthalimide [47], azulene [48], metal-oxide nanowire [49], polymer brushes [50], and polyimide [51]. Because this spectroscopic method is an infrared spectroscopic method, it is useful because it is applicable to non-crystalline materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group reported the highly oriented structure of Nafion thin films on SiO x [34], MgO [35,36], sputtered Pt [37], and sputtered Au [36] surfaces by infrared p-polarized multiple-angle incidence resolution spectrometry (pMAIRS), which was developed by Hasegawa and co-workers [38][39][40], as presented in Figure 2(a-d). IR pMAIRS offers the molecular orientation for each functional group to various functional materials such as derivatives of polythiophene [41,42], porphyrin [43], pentacene [44], fullerene [45], naphthalene diimide [46], phthalimide [47], azulene [48], metal-oxide nanowire [49], polymer brushes [50], and polyimide [51]. Because this spectroscopic method is an infrared spectroscopic method, it is useful because it is applicable to non-crystalline materials.…”
Section: Introductionmentioning
confidence: 99%
“…Because this spectroscopic method is an infrared spectroscopic method, it is useful because it is applicable to non-crystalline materials. In combination with X-ray scattering technique, it is useful to discuss the structure of crystalline and amorphous parts in other materials [43,44,47,48,[52][53][54]. It also makes it possible to discuss the substrate dependence in greater detail [25,36,37] or casting solvent dependence [43,54] of the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%
“…Yokoyama and co-workers demonstrated that several amorphous materials containing pyridine rings exhibited face-on orientation due to intermolecular hydrogen bonding. 17,18 Using a similar approach, a star-shaped phthalimide-based molecule has recently been designed by Nakamura et al 19 This compound has three N-H/O hydrogen bonding sites forming a 2D supramolecular structure, yielding face-on orientation. Therefore, molecular design considering anisotropic intermolecular interactions is an important chemical strategy for controlling molecular orientation.…”
mentioning
confidence: 99%
“…This is supported by the out-of-plane X-ray diffraction data of the thin films (Figure 5), in which TAT showed no recognizable diffraction peak, while the other two showed multiple peaks that could be assigned to crystal planes of the corresponding single-crystal X-ray structures [34,35]. The amorphousness of TAT is reasonable if one considers its large conformational flexibility originating from rotation of the six single bonds, in addition to the general low crystallinity of branched molecules [26][27][28][29][30]. The smoothness of the TAT film enabled us to define the effective thickness and thus to estimate charge-carrier mobility by the SCLC method.…”
Section: Thin-film Characteristicsmentioning
confidence: 96%
“…Molecules with a branched backbone, including windmill-shaped ones, are known to form amorphous, smooth films, and to show decent charge-carrier mobilities upon proper molecular design. As such, branched molecular structures have been continuously featured in the design of organic semiconductors [26][27][28][29][30]. On the other hand, morphological behaviour of molecules in the deposition by the photoprecursor approach is often dissimilar from that in conventional techniques, largely because of the change in molecular structure during the solid-state photoreaction [16,17].…”
Section: Figurementioning
confidence: 99%